Member competence, group interaction, and group decision making: A longitudinal study. - Watson, Warren E.; Michaelsen, Larry K.; Sharp, Walt (Journal of Applied Psychology, 1991)
The primary objective of this study was to examine the extent to which increased experience in working in a group would affect group versus individual problem solving. The duration and intensity of group involvement for subjects (over 30 hr) was extensive. In addition, the reward system provided a clear and direct tie between individual or group performance and a significant outcome (i.e., course grades). The decision-making task had a great deal in common with many of the aspects of group decision making in organizations. Results were overwhelming in favor of group decision making across time, given this type of task.